2021
DOI: 10.1007/s00428-020-03015-z
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and molecular classification of lung neuroendocrine neoplasms

Abstract: Neuroendocrine neoplasms (NENs) of the lung encompass neuroendocrine tumors (NETs) composed of typical (TC) and atypical (AC) carcinoids and full-fledged carcinomas (NECs) inclusive of large cell neuroendocrine carcinoma (LCNEC) and small cell carcinoma (SCLC). NETs and NECs are thought to represent distinct and separate lesions with neither molecular overlap nor common developmental continuum. Two perspectives were addressed regarding the morphologic and molecular classification of lung NENs: (i) a supervised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 82 publications
0
47
0
2
Order By: Relevance
“…Prior studies in the context of pulmonary NECs have suggested several biological differences between pulmonary LC and SC NECs. These differences have been shown to impact prognosis as well as treatment responsiveness 11,12 . Whether these biological traits carry the same weight among patients with digestive SC versus LC NECs is unclear and this is an area of unmet need in GEP‐NEN research.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in the context of pulmonary NECs have suggested several biological differences between pulmonary LC and SC NECs. These differences have been shown to impact prognosis as well as treatment responsiveness 11,12 . Whether these biological traits carry the same weight among patients with digestive SC versus LC NECs is unclear and this is an area of unmet need in GEP‐NEN research.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting marker is insulinoma-associated protein 1 (INSM1), which reflects true neuroendocrine differentiation [ 31 ]. For future studies, it would be of interest, whether these histopathological parameters could also be reflected by quantitative imaging analysis, including the biological heterogeneity of pNET [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer starts in the lungs and progresses to the brain. Despite this, the lung cancer detection procedure is very ineffective because doctors will only be able to detect the illness after it has progressed to an advanced stage (Metovic, et al 2021, Abdullah and Abdulazeez, 2021, Malika, and Jaina, Yuvaraj, et al 2021.…”
Section: Introductionmentioning
confidence: 99%